2018
DOI: 10.1021/acs.jpcc.8b06845
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Photocarrier Relaxation in Graphene Achieved by Epitaxial Growth: Ultrafast Photoluminescence Decay of Monolayer Graphene on SiC

Abstract: Acceleration of photocarrier relaxation in graphene results in the enhancement of its properties for graphene-based ultrafast optical devices. The acceleration can be achieved by utilizing the relaxation paths outside the graphene to avoid bottlenecks in the graphene for photocarrier relaxation. In this study, we investigate photocarrier relaxation in epitaxial and transferred monolayer graphene on SiC with a buffer layer at room temperature by means of time-resolved photoluminescence spectroscopy. The photolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 47 publications
3
24
0
Order By: Relevance
“…However, a counterintuitive feature is that the temperature-dependent decreasing rate of emission intensity of BiOBr-V is much slower than that of BiOBr case, since promoted exciton-phonon couplings usually lead to faster decays in other systems. [36,37] Besides, time-resolved photoluminescence tests also give counterintuitive results. Time-resolved fluorescence spectra monitoring at 470 nm (corresponding to the short-lived excitonic emission peak; Figure 3d) verify that BiOBr-V possesses a slower excitonic radiative decay than BiOBr.…”
Section: Page 10 Of 22 Ccs Chemistrymentioning
confidence: 99%
“…However, a counterintuitive feature is that the temperature-dependent decreasing rate of emission intensity of BiOBr-V is much slower than that of BiOBr case, since promoted exciton-phonon couplings usually lead to faster decays in other systems. [36,37] Besides, time-resolved photoluminescence tests also give counterintuitive results. Time-resolved fluorescence spectra monitoring at 470 nm (corresponding to the short-lived excitonic emission peak; Figure 3d) verify that BiOBr-V possesses a slower excitonic radiative decay than BiOBr.…”
Section: Page 10 Of 22 Ccs Chemistrymentioning
confidence: 99%
“…In addition, the extracted diffusion coefficient of the excitons was reduced by approximately four times from the bare WS 2 monolayer to the fully encapsulated monolayer due to the scattering by additional phonons introduced by hBN 42 . In a few studies on graphene, it has been found that the photocarrier lifetimes of CVD-grown graphene transferred to hBN are shorter than those of graphene transferred to SiO 2 81 , and photocarriers in graphene epitaxially grown on SiC substrates relax faster than those in graphene transferred to SiC substrates 82,83 . These discrepancies have been attributed to the difference in the coupling between photocarriers in the graphene layers and phonons in the substrates.…”
Section: Phonon-assisted Relaxationmentioning
confidence: 99%
“…Our recent study pertaining to PL from epitaxially grown and transferred MLG on SiC demonstrated that the PL decay of a transferred MLG was slower than that of an epitaxial MLG. 6 The distance between the graphene and substrate was longer in the transferred graphene sample than in the epitaxial graphene sample, thereby explaining the slower heat flow in the transferred graphene sample. A slow heat flow causes a slow PL decay, resulting in a strong steady-state PL.…”
Section: ■ Introductionmentioning
confidence: 99%